Peningkatan Potensi Badan Usaha Milik Desa (BUMDes) Sebagai Wujud Ekonomi Kreatif Desa Trasan - Muhdiyanto Muhdiyanto; Indah Nur Kusuma Ningrum; Nella Atalia Zahra; Annisa Putri Damayanti; Frisky Nicko Manfaaturohmansyah; Rismadi Indria Alfarizy (Edumedia Solution, 2022)
Revenue from Trasan BUMDes has not reached the target return, this is because the establishment of BUMDes coincides with the COVID-19 pandemic. One way to deal with the challenges and obstacles faced by BUMDes is to develop business continuity by applying creative economic entrepreneurial knowledge. PPMT team discussions with partners, we propose a method for BUMDes for development in marketing. The hope of the team after the training and mentoring of BUMDes is that the village can improve the economy and development so that the welfare of the community can increase. In writing, the output of the activity is in the form of a final report, publication of scientific articles, and publication of activities in the mass media (online offline), as well as video publications for marketing.